Revalorization of selected municipal solid wastes as new precursors of “green” nanocellulose via a novel one-pot isolation system: A source perspective - Chen, You Wei; Lee, Hwei Voon (Elsevier, 2018)
In the present work, four types of newly chosen municipal solid wastes (Panax ginseng, spent tea residue, waste cotton cloth, and old corrugated cardboard) were studied as the promising sources for nanocellulose, which has efficiently re-engineered the structure of waste products into highly valuable nanocellulose materials. The nanocellulose was produced directly via a facile one-pot oxidative hydrolysis process by using H2O2/Cr(NO3)3 solution as the bleaching agent and hydrolysis medium under acidic condition. The isolated nanocellulose products were well-characterized in terms of chemical composition, product yield, morphological structure and thermal properties. The study has found that the crystallinity index of the obtained nanocellulose products were significantly higher (62.2–83.6%) than that of its starting material due to the successive elimination of lignin, hemicellulose and amorphous regions of cellulose, which were in good agreement with the FTIR analysis. The evidence of the successful production of nanocellulose was given by TEM observation which has revealed the fibril widths were ranging from 15.6 to 46.2 nm, with high cellulose content (>90%), depending on the cellulosic origin. The physicochemical properties of processed samples have confirmed that the isolation of high purity nanocellulose materials from different daily spent products is possible. The comparative study can help to provide a deep insight on the possibility of revalorizing the municipal solid wastes into nanocellulose via the simple and versatile one-pot isolation system, which has high potential to be used in commercial applications for sustainable development.